2009
DOI: 10.1590/s1519-566x2009000600019
|View full text |Cite
|
Sign up to set email alerts
|

Atração de adultos de Sphenophorus levis Vaurie (Coleoptera: Curculionidae) a fragmentos vegetais em diferentes estados de conservação

Abstract: -The occurrence of the sugarcane weevil Sphenophorus levis Vaurie is important in sugarcane in some regions in Brazil. Damage is caused by the larvae as they bore into the nodes and can reach 30 ton/ha/year. Many control alternatives have been attempted, but none were satisfactory, except for the use of toxic baits. Therefore, it is necessary to optimize their effi ciency or to propose new techniques. The objective of the current study was to evaluate the attractiveness of adults of S. levis to sugarcane nodes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 5 publications
(10 reference statements)
0
8
0
Order By: Relevance
“…Although EA exerts an interchangeable effect with ET and other alcohols on the olfactory response of other coleopteran species (Lin and Phelan, 1991), the use of EA at the same ratio in all the combinations, evaluated in this study, was probably unable to increase H. hampei attractiveness compared to ET:MT. Also, Girón-Pérez et al (2009) revealed that the production of ET in plant substrates is higher than EA over time, suggesting that the ratio of the ester EA in the mixture should probably be lower in relation to the alcohols ET and MT. Perhaps other compounds should be added to potentiate the synergistic effect among the volatiles found in greatest proportions in the mature fruits, i.e., aldehydes (Sulaeha et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Although EA exerts an interchangeable effect with ET and other alcohols on the olfactory response of other coleopteran species (Lin and Phelan, 1991), the use of EA at the same ratio in all the combinations, evaluated in this study, was probably unable to increase H. hampei attractiveness compared to ET:MT. Also, Girón-Pérez et al (2009) revealed that the production of ET in plant substrates is higher than EA over time, suggesting that the ratio of the ester EA in the mixture should probably be lower in relation to the alcohols ET and MT. Perhaps other compounds should be added to potentiate the synergistic effect among the volatiles found in greatest proportions in the mature fruits, i.e., aldehydes (Sulaeha et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Later in vegetation, sugar beets are increasingly attacked by a variety of pests as a result of favorable weather conditions. In this "unprotected" sugar beet period pheromone traps comprise one of the most effective methods for monitoring the seasonal flight dynamics of adult male moths [29][30][31]. These traps are often used to detect the presence of pests by season and location within a facility and to monitor apparent changes in the size of pest population over time [32].…”
Section: Moths On Sugar Beetsmentioning
confidence: 99%
“…However, during transfer, harvested material may fall on the ground, which may be infested with the pest or be attractive to sugarcane billbug due to the release of volatiles during the fermentation process of the fallen material. 17,18 We hypothesize that areas near the transfer sites are more prone to be infested by the sugarcane billbug compared to more distant ones, as individuals are attracted by emitted volatiles in crop residues. The main objective of this work was therefore to determine how the spatiotemporal distribution of S. levis injury is affected by load transfer sites in commercial sugarcane fields.…”
Section: Introductionmentioning
confidence: 99%